Complexity of Tumor Microenvironment: Therapeutic Role of Curcumin and Its Metabolites. (13th December 2022) - Prasad, Sahdeo; Saha, Priyanka; Chatterjee, Bilash; Chaudhary, Anis Ahmad; Lall, Rajiv; Srivastava, Amit K
Abstract: The tumor microenvironment (TME) is a complex network of cellular and non-cellular components surrounding the tumor. The cellular component includes fibroblasts, adipocytes, endothelial cells, and immune cells, while non-cellular components are tumor vasculature, extracellular matrix and signaling molecules. The tumor cells have constant close interaction with their surrounding TME components that facilitate their growth, survival, and metastasis. Targeting a complex TME network and its interaction with the tumor can offer a novel strategy to disrupt cancer cell progression. Curcumin, from turmeric rhizome, is recognized as a safe and effective natural therapeutic agent against multiple diseases including cancer. Here the effects of curcumin and its metabolites on tumor-TME interaction modulating ability have been described. Curcumin and its metabolites regulate TME by inhibiting the growth of its cellular components such as cancer-associated adipocytes, cancer-associated fibroblast, tumor endothelial cells, tumor-stimulating immune cells, and inducing anticancer immune cells. They also inhibit the interplay of tumor cells to TME by suppressing non-cellular components such as extracellular matrix, and associated tumor promoting signaling-pathways. In addition, curcumin inhibits the inflammatory environment, suppresses angiogenic factors, and increases antioxidant status in TME. Overall, curcumin has the capability to regulate TME components and their interaction with tumor cells.